Pengaruh Kenaikan Suhu Terhadap Stabilitas Jembatan Rangka Baja - Russeno Wirapradja (Direktorat Bina Teknik Jalan dan Jembatan, 1992)
The objective of the project was to study the influence of opposed right-turns on saturation flow. It was intended to use this as a tool for design and timing of signalised intersections because no guidance procedure was available in Indonesia.Data was collected from two signalised intersections in Bandung by video-camera, three theoretical models were discussed and applied to the collected data and then compared with the observations. The theoretical methods increasingly over estimatd the saturation flow at higher approach width.Generally good correlations were obtained between observed saturation flow, approach width and opposing flow. However, thus was not the case regarding the ratio of right-turns.Field observations showed that the right-turning vehicles did not give way to opposing flow, which is an important difference between Indonesian and Western traffic behaviour. Therefore, it its necessary to develop a model for capacity calculations applicable to Indonesian conditions based on further data collection for a wide range of conditions and sites.